An industry 4.0 self description information model for software components contained in the administration shell - Neto, Luís (2019)
Industry 4.0 is the movement towards a fourth industrial revolution that will consist in the digitization and integration of all value chain. In Europe, this movement is led by the German RAMI 4.0 (Reference Architecture for Industry 4.0) proposal, which is attracting a lot of attention from industry, academia and other practitioners. Under the RAMI 4.0 scope there is an Administration Shell proposal to abstract physical and logical assets in a standardized way. Once abstracted, assets become Industry 4.0 Components and can be fully integrated in the Cyber Physical Production System or value chain. This work focuses on the utilization of software components within the Administration Shell. There is a necessity to represent software components and their relation to industrial asset. Therefore, control and monitoring applications involving software components and other assets can be represented in compliance with the I4.0 Component Model. To address this necessity the Smart Object Self Description information model is proposed and applied to a real case study scenario.